District Expert Opinion Process in Forensic Autopsies - Can, İsmail Özgür and Özdemir, Mehmet Hakan and Arıcan, Nadir and Uysal, Cafer (The Bulletin of Legal Medicine, 2011)
By the implementation of Criminal Procedure Law in 2004, new arrangements related to expert opinion put into practice. A district physician like official expert could be invited by plaintiff or defendant lawyer to be present and give expert opinion in forensic autopsies. Nevertheless die responsibility and the role of the district physician in process is still dilemma. The aim of the study is to share the experiences of forensic medicine specialists in the process of forensic autopsies of two cases as district medical examiner invited by defendants and family members of deceased. Cases were; a twenty nine year old man, death reported due to torture and inhuman treatment in custody and a twenty one year old man death reported due to shooting by police during a student riot. For this aim, we discussed and share the process with the experiences of official and expert witness of forensic medicine specialists and defendants after accepting the expert role, experiences before, during and after the autopsies and medico legal reporting. Key words: forensic autopsy, official expert, expert witness.